School Quality Development Strategy Through Teachers’ Performance and Facilities at SMP Negeri 4 Palembang - Achmad Asyaari; Nur Ahyani; Darwin Effendi (Journal of Social Work and Science Education, 2026)
This study aims to investigate the quality development approach at SMP Negeri 4 Palembang, which faces issues related to improving educational quality amid problems concerning inconsistent teacher performance and inadequate facilities. The core of this study is to formulate strategies for enhancing school quality, analyzed through two main components: teacher performance and availability of facilities. This study employs a qualitative approach at SMP Negeri 4 Palembang, with sources consisting of teachers, students, school officials (Principal and Administrative Staff), as well as students’ parents. Data analysis was conducted using the interactive model of Miles & Huberman, which includes the stages of data reduction, data presentation, and drawing conclusions. The findings of this study indicate that quality development at this school needs to focus on two main aspects. First, although most educators have good pedagogical competence (80% of interview results), there is a major challenge in the lack of integration of Information and Communication Technology (ICT), which requires immediate attention (70% of observations). Second, facilities are generally supportive for basic learning activities; however, there is a significant shortage in science laboratory facilities and supporting tools for practical learning (70% of the data indicate an urgent need). Recommended steps include implementing intensive and continuous ICT training programs for teachers to encourage innovation in digital learning, as well as upgrading and procuring more complete and modern laboratory equipment. The conclusion of this study emphasizes that quality development must be conducted holistically and sustainably, where improving teacher performance and fulfilling infrastructure serve as crucial inputs to achieve educational outcomes.